An Analysis of Interferences Sasak’s Accent into English: A Case Study of Local Guider in Tete Batu Tourism Village East Lombok - M. Ubaidillah Karomi Safari; Dzoharat Nabilah Mas (CV. Kalimasada Group Profesional, 2024)
This study described the use of Sasak’s accents in tour guides when speaking English. The approach to this study was qualitative. The type of research used was a case study. The data analysis technique used descriptive qualitative. The formulation of the problem in this study was how Sasak’s accent affects tour guides when speaking English. The purpose of this study was to determine the description of the Sasak’s accent process when tour guides speak English. Data collection techniques use observation, interviews, recording and documentation. The research subjects were local guider in Tete Batu tourist area with English language proficiency levels such as intermediate and advanced. The results of this study were: 1) There were differentiation of consonants between Sasak and English which being basic triggers for local guider problems in pronouncing English such as the letters /F/ and /V/. These letters do not exist in Sasak’s accent, while in English these letters always exist and always pronouncing clearly in every English word. 2) Sasak’s accent is a strong accent so that it is one of the triggers that interferes with the performance of local guider in speaking English. 3) Sasak language is the dominant language that is always used by the Sasak ethnic group in Lombok.